2017
DOI: 10.5194/acp-17-7733-2017
|View full text |Cite
|
Sign up to set email alerts
|

Improved provincial emission inventory and speciation profiles of anthropogenic non-methane volatile organic compounds: a case study for Jiangsu, China

Abstract: Non-methane volatile organic compounds (NMVOCs) are the key precursors of ozone (O 3 ) and secondary organic aerosol (SOA) formation. Accurate estimation of their emissions plays a crucial role in air quality simulation and policy making. We developed a high-resolution anthropogenic NMVOC emission inventory for Jiangsu in eastern China from 2005 to 2014, based on detailed information of individual local sources and field measurements of source profiles of the chemical industry. A total of 56 NMVOCs samples wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 52 publications
2
66
0
Order By: Relevance
“…Through a systematic literature review, we found that the anthropogenic VOC emission inventory methodologies are similar, but the source classification and EFs used in some studies are different. Thus, this study combined the existing source classification system, EF databases, and source profile databases, followed by establishing the emission inventory in the BTH region (Bo et al, 2008;Wu et al, 2016a;Zhao et al, 2017;Zhong et al, 2017). A detailed description of the method is provided below.…”
Section: Establishment Of the Anthropogenic Voc Emission Inventorymentioning
confidence: 99%
See 1 more Smart Citation
“…Through a systematic literature review, we found that the anthropogenic VOC emission inventory methodologies are similar, but the source classification and EFs used in some studies are different. Thus, this study combined the existing source classification system, EF databases, and source profile databases, followed by establishing the emission inventory in the BTH region (Bo et al, 2008;Wu et al, 2016a;Zhao et al, 2017;Zhong et al, 2017). A detailed description of the method is provided below.…”
Section: Establishment Of the Anthropogenic Voc Emission Inventorymentioning
confidence: 99%
“…Moreover, emission inventories are essential input data for the chemical transport model (Hodzic et al, 2010;Coll et al, 2010). Since the pioneering study by Piccot et al (1992), the "Emission Factor (EF) method" has been widely used to establish emission inventories, which estimates the emissions of VOC sources by multiplying the corresponding activities and detailed EFs (Tonooka et al, 2001;Klimont et al, 2002;Ohara et al, 2007;Bo et al, 2008;Zhang et al, 2009;Zheng et al, 2009;Wu et al, 2016a;Huang et al, 2017;Janssens-Maenhout et al, 2015). The characterization and quantification of VOC emissions is highly complicated, as the emission sources of VOCs exhibit complexity and diversity (Borbon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…VOCs emitted from biogenic, pyrogenic and anthropogenic sources and their respective amounts depend on several parameters, including temperature, humidity and plant species [6]. The results of the bottom-up ground VOC emissions inventory indicated that anthropogenic activities, such as industrial processes and solvent use, make important contributions, and these emissions were estimated to increase [7]. Alkanes, aromatics and oxygenated VOCs (OVOCs) were the most important species, accounting for 25.9-29.9, 20.8-23.2 and 18.2-21.0% of the total annual anthropogenic emissions, respectively [7].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the bottom-up ground VOC emissions inventory indicated that anthropogenic activities, such as industrial processes and solvent use, make important contributions, and these emissions were estimated to increase [7]. Alkanes, aromatics and oxygenated VOCs (OVOCs) were the most important species, accounting for 25.9-29.9, 20.8-23.2 and 18.2-21.0% of the total annual anthropogenic emissions, respectively [7]. However, NMVOC emissions inventories have large uncertainties because of the limited data on activity rates and emission factors for a wide variety of VOCs [8].…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen as well in the table, the aggregated amount of fertilizer using by province were close to the provincial-level statistics, and the deviation relevant to the official statistics was 2.3% for the whole YRD. The methods and data sources for activity levels of other source categories were provided in our previous studies (Zhou et al, 2017;Zhao et al, 2017;Yang and Zhao, 2019).…”
Section: Emission Inventory Based On Constant Emission Factors (E1)mentioning
confidence: 99%